2019
DOI: 10.1016/j.humimm.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical B cell functions in transplantation

Abstract: B cells are differentiated to recognize antigen and respond by producing antibodies. These activities, governed by recognition of ancillary signals, defend the individual against microorganisms and the products of microorganisms and constitute the canonical function of B cells. Despite the unique differentiation (e.g. recombination and mutation of immunoglobulin gene segments) toward this canonical function, B cells can provide other, "non-canonical" functions, such as facilitating of lymphoid organogenesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 245 publications
0
8
0
Order By: Relevance
“…B lymphocytes differentiate from lymphoid stem cells of the bone marrow and play indispensable roles in humoural immunity via the secretion of antibodies and cytokines 61 (Figure 3, Table 2). Histology and immunohistochemistry showed that polyclonal plasma cells (which produce immunoglobulin (Ig)M, IgA and IgG) were absent from the calcified aortic valve.…”
Section: The Role Of B Cells In Atherosclerosis and Calcificationmentioning
confidence: 99%
“…B lymphocytes differentiate from lymphoid stem cells of the bone marrow and play indispensable roles in humoural immunity via the secretion of antibodies and cytokines 61 (Figure 3, Table 2). Histology and immunohistochemistry showed that polyclonal plasma cells (which produce immunoglobulin (Ig)M, IgA and IgG) were absent from the calcified aortic valve.…”
Section: The Role Of B Cells In Atherosclerosis and Calcificationmentioning
confidence: 99%
“…In this period, the immune system and the tumor adapt to each other and the repertoire of tumor cells that survived the first epoch is “sculpted” to select cells expressing variants least recognizable by effector cells and/or to enforce tumor-induced immunosuppression. We should add that a condition we first described in transplantation and named “accommodation” to reflect acquired resistance to immune or inflammatory injury probably occurs in the first and/or second epoch and renders tumor cells inured to immune-mediated cytotoxicity [82,83,84]. In the third epoch, ongoing diversification and accommodation generates tumor cells that escape control by innate and adaptive immunity, chemotherapy, and so forth, and progression is manifest.…”
Section: Extrinsic Defenses Against Malignancy—tumor Immunitymentioning
confidence: 99%
“…Accommodation is also postulated to benefit tumors and facilitate host defense against infection. 78,125 The set of mechanisms that overcome antibody-mediated injury and resist subsequent injury are yet to be fully elucidated. There is general agreement that cells, tissues and organs targeted by antibodies must have at least normal if not increased ability to resist complement-mediated cytotoxicity.…”
Section: Accommodationmentioning
confidence: 99%
“…73,74 Indeed, if alloantibodies had any impact on tumor or skin allografts, it was to prolong rather than to shorten graft survival. 75 It is now appreciated that alloantibodies can repair and protect grafts by one or more of several mechanisms, as we later discuss and elsewhere review 33,[76][77][78] ; however, the beneficial properties of alloantibodies are only observed when antibodies fail to exert full effector functions on grafts. What prevents alloantibodies from attacking tumor and tissue grafts with full effector function is the positioning of endothelium of the recipient between the alloantibodies and the graft.…”
Section: Spatial Separation Of Antibodies and Antigenmentioning
confidence: 99%
See 1 more Smart Citation